An engineering review of external fixators. (December 2021) - Fernando, P.L.N.; Abeygunawardane, Aravinda; Wijesinghe, PCI; Dharmaratne, Parakrama; Silva, Pujitha
Highlights: Mechanical stability plays a key role in the effectiveness of external fixators. Strength and stiffness are the main factors which contributes towards stability. Modified configurations of linear, circular and hybrid fixators are investigated. Light weight composite materials are gradually replacing traditional metallic alloys. Existing research gaps in further optimizing external fixators are identified. Abstract: External Fixators are a common technique used to treat a variety of issues related to bones, predominantly due to its non-intrusive nature and versatility in terms of form and materials. While it is mainly used to treat open fractures, its other uses include limb lengthening, deformity correction, bone grafting, compression of non-unions and stabilization of dislocations. Its earliest use dates as far back as 400 BCE and has undergone significant improvements, focusing on both customization and optimization. These two aspects highlight the significance of complementing the orthopaedic requirements with engineering knowledge and its applications. Hence, this review paper aims to conduct an examination of recent developments of external fixators with a special focus on its structure, the usage of materials and biomechanical investigations using experimental and numerical techniques. The paper presents the existing level of engineering knowledge with regards to these aspects and identifies research gaps, which can improve the quality of the commonly used external fixators.